The nominative cases of nouns in the interpretation of (Uyun al-Tafasir by al-Fudala’ al-Samasir): A descriptive and analytical study - البرزنجي, دلسوز جعفر; عەزيز, Faraidun ئەحمد (Sulaimani Journal for Humanities, 2019)
After the Arabic language linguists had established its foundational grammatical rules and the users of the language observed those rules, the best area where those grammatical and linguistic rules were realized and applied was Qur’an exegeses. The scholars of the Qur’an exegesis clearly discussed and investigated all the Arabic grammatical rules while trying to explicate the Qur’an. That is why conducting research about those Qur’an exegeses now means reviewing the Arabic language grammar. To do so, the researcher has chosen the Turkish Sheikh Sahabaddin Siwasi’s exegesis of Qur’an. His exegesis is permeated with linguistic viewpoints that deserve to be studied in detail. In Siwasi’s exegesis, the researcher has chosen the topic of Al-Marfū’at; he discusses Siwasi’s perspectives by investigating their origins in the traditional and modern linguistic books.